Activation of the Farnesoid X Receptor (FXR) Suppresses Linoleic Acid-Induced Inflammation in the Large Yellow Croaker (Larimichthys crocea). Issue 9 (2nd July 2020) - Du, Jianlong; Chen, Qiang; Li, Yongnan; Xiang, Xiaojun; Xu, Wei; Mai, Kangsen; Ai, Qinghui
ABSTRACT: Background: High linoleic acid (LA) intake leads to inflammation that adversely influences health in fish. However, whether the farnesoid X receptor (FXR) could be an effective target for regulating LA-induced inflammation remains unknown. Objective: The purpose of this study was to investigate the role of FXR in the regulation of LA-induced inflammation in large yellow croakers. Methods: Large yellow croakers (initial weight of 10.03 ± 0.02 g) were allocated to 4 groups and fed a fish oil diet (6% FO), a soybean oil diet (6% SO), or the SO diet supplemented with 300 or 900 mg chenodeoxycholic acid (CDCA)/kg for 10 wk. The cultured kidney cell line PCK and primary hepatocytes from large yellow croakers were stimulated by LA (50 μM) after pretreatment with an FXR ligand (GW4064 or CDCA) or transfection with fxr- small interfering RNA (siFXR). mRNA expression of proinflammatory genes in the head kidney and liver tissues, PCK cells, and primary hepatocytes was determined by qPCR. The luciferase reporter assay, electrophoretic mobility shift assay, and immunoprecipitation assay were conducted in HEK 293T cells to determine the transcriptional activity of P65 and protein interactions between P65 and FXR or the small heterodimer partner (SHP). Results: Proinflammatory genes were 93–1180% higher in the SO group compared with the FO group. CDCA supplementation decreased mRNA expression of proinflammatory genes by 17–87% while increasing fxr and shp expression by 120–460%. In PCK cells and primary hepatocytes, ligand-mediated activation of FXR decreased the LA-induced expression of proinflammatory genes by 18–67%, whereas siRNA-mediated knockdown of FXR increased the LA-induced expression of proinflammatory genes by 64–96%. FXR bound to the promoter of shp and regulated its mRNA expression. Both FXR and SHP could bind to P65 to suppress the transcriptional activity of P65. Conclusions: These results indicate that FXR has anti-inflammatory properties in large yellow croakers by directly and indirectly suppressing NFκB activity.